Introducing the HTML5 Web Speech API : your practical introduction to adding browser-based speech capabilities to your websites and online applications - Libby, Alex (Apress L.P., 2020)
Leverage the power of HTML5 Web Speech API to quickly add voice capabilities to your websites. This project-oriented book simplifies the process of setting up and manipulating the API in the browser using little more than a text editor or free software. You'll be presented with a starting toolset that you can use to develop future projects, incorporate into your existing workflow and allow you to take your websites to the next level, reducing the reliance on entering choices through a keyboard and making the overall experience easier for customers. This excellent resource is perfect for getting acquainted with creating and manipulating browser-based APIs. You dont have to convert your whole work process immediately; you can incorporate as little or as much as you want of the API, and build on this as your skills develop. We live in an age where speed and simplicity are of the essence - this book provides a perfect way to add speech capabilities to our websites, directly in the browser and with the minimum of fuss. Introducing the HTML5 Web Speech API is the right choice for developers who want to focus on simplicity to produce properly optimized content in modern browsers using tools already in their possession. You will: Implement the Web Speech API in a project Explore some of the options for personalizing them for a project Gain an appreciation of pointers around user experience and how this affects the API Understand how to manage issues and security when using the API Work through some example projects, from standalone demos to implementing with other tools or libraries.